Three new species and new records of the genus Centromerus (Araneae, Linyphiidae) from Italy - Ballarin, Francesco; Pantini, Paolo (European Journal of Taxonomy, 2020)
Three new species of the genus Centromerus from Italy, C. tongiorgii sp. nov., C. hanseni sp. nov., and C. gatoi sp. nov., are described for the first time on the basis of both male and female specimens. Their relationships with other congeneric species, as well as their diagnoses, are discussed using morphological characters. New records of poorly known species of Centromerus from Italy are furthermore reported. Among them, C. desmeti Bosmans, 1986 is reported for the first time for the Italian fauna and for continental Europe.